2019
DOI: 10.1017/s1047951119001070
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion imaging has the possibility to detect liver abnormalities in young Fontan patients with good hemodynamics

Abstract: Introduction:Liver fibrosis and cirrhosis are one of the critical complications in Fontan patients. However, there are no well-established non-invasive and quantitative techniques for evaluating liver abnormalities in Fontan patients. Intravoxel incoherent motion diffusion-weighted imaging with MRI is a non-invasive and quantitative method to evaluate capillary network perfusion and molecular diffusion. The objective of this study is to assess the feasibility of intravoxel incoherent motion imaging in evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A study by Shiraga et al revealed that IVIM technique could differentiate pre-fibrotic liver states in young Fontan patients without any influence from central venous pressure. 58 Decreased PF was also shown to have the potential to predict hepatic venous pressure gradient in liver cirrhosis. 59 Li et al identified a potential correlation between lower PF, D fast , and serum liver function biomarkers, 50 contributing to the evaluation of liver function.…”
Section: Liver Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Shiraga et al revealed that IVIM technique could differentiate pre-fibrotic liver states in young Fontan patients without any influence from central venous pressure. 58 Decreased PF was also shown to have the potential to predict hepatic venous pressure gradient in liver cirrhosis. 59 Li et al identified a potential correlation between lower PF, D fast , and serum liver function biomarkers, 50 contributing to the evaluation of liver function.…”
Section: Liver Fibrosismentioning
confidence: 99%
“…IVIM also has a wide range of applications in fibrosis‐related diseases. A study by Shiraga et al revealed that IVIM technique could differentiate pre‐fibrotic liver states in young Fontan patients without any influence from central venous pressure 58 . Decreased PF was also shown to have the potential to predict hepatic venous pressure gradient in liver cirrhosis 59 .…”
Section: Liver Fibrosismentioning
confidence: 99%
“…Studies[ 12 , 44 , 45 ] have shown that the D, D* and f values of hepatic fibrosis patients were significantly lower than those in normal control groups. The IVIM-DWI parameters D, D* and f can be used to distinguish healthy people from patients with hepatic fibrosis, with the f value exhibiting the best diagnostic value[ 38 ].The study by Shiraga et al[ 36 ] showed that IVIM-DWI also identified a pre-fibrotic state of the liver in Fontan patients. The study included five consecutive Fontan patients and four age-matched healthy volunteers.…”
Section: Hepatic Fibrosismentioning
confidence: 99%